2020
DOI: 10.2106/jbjs.oa.19.00067
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Muscle Reinnervation at the Time of Major Limb Amputation in Traumatic Amputees

Abstract: Background: Orthopaedic trauma etiologies are a common cause for amputation. Targeted muscle reinnervation (TMR) is a technique aimed at reducing or preventing pain and improving function. The purpose of this study was to examine postoperative phantom limb pain and residual limb pain following TMR in orthopaedic trauma amputees. In addition, postoperative rates of opioid and neuromodulator medication use were evaluated. Methods: Twenty-five patients (60% male) prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 44 publications
0
70
0
1
Order By: Relevance
“…Finger amputation happen more often due to trauma (31,32,42,43). In contrast to major limb amputations where oncologic disease, diabetes and vascular disease are responsible for the majority of the indication (33)(34)(35)(36)(37)(38)41). If in major limb amputation a trauma is the cause, the trauma mechanism is more invasive and often more than the affected limb is injured (38).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finger amputation happen more often due to trauma (31,32,42,43). In contrast to major limb amputations where oncologic disease, diabetes and vascular disease are responsible for the majority of the indication (33)(34)(35)(36)(37)(38)41). If in major limb amputation a trauma is the cause, the trauma mechanism is more invasive and often more than the affected limb is injured (38).…”
Section: Discussionmentioning
confidence: 99%
“…Frantz et al reported incidences outcomes after TMR in major amputation of both upper and lower limb. Fourty percent of their patients had RLP at final follow-up (37). The use of opioid medication at final follow up was 16%, of which all patients used opioid medication preoperatively.…”
Section: Targeted Muscle Reinnervationmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Furthermore, TMR has also served to prevent postoperative pain if performed at the time of limb amputation. [43][44][45] Valerio et al established that preemptive management of postamputation pain with TMR resulted in significantly reduced PLP and residual limb pain compared with the untreated amputee cohort. 44 Recently, TMR in the hand has been studied to examine motor entry points (MEPs) to the intrinsic muscles.…”
Section: Traumatic Injury Management Optionsmentioning
confidence: 99%